Lies my teacher told me : everything American history textbooks get wrong - Loewen, James W.; Stefoff, Rebecca, 1951- (The New Press, 2019)
Presents the classic history book adapted into a version for readers ages twelve through eighteen. Highlights various moments of history without watering down the difficult or controversial aspects of them as classroom text books often do. Includes maps and photographs.